Form og tonal disposition i Alexander Zemlinskys ‘Lyrische Symphonie’ - Michelsen, Thomas (Danish Yearbook of Musicology, 1997)
Form and tonal layout in Alexander Zemlinsky’s ‘Lyrische Symphonie’ The composer and conductor Alexander Zemlinsky (1871-1942) played an important part in establishing the modernity which marked the musical life of Vienna around the turn of the century. This article contains a brief survey of the three stylistic periods into which Zemlinsky’s works may be divided. It is proposed that the dividing line between the early, Brahmsian period and the second, in which modernity marks Zemlinsky’s compositional style, be placed before rather than, as suggested by Rudolf Stephan, after 1900. The main part of the article is an analytical survey of the relationship between form and tonality in Zemlinsky’s chief symphonic work: Lyrische Symphonie op. 18 (1922-23). It is pointed out that the sonata form scheme of the first movement, which combines sonata form with strophic song form, as well as the overall formal layout of the work are held together by a fundamental ‘frame tonality’ in spite of the fact that tonality on a detailed level is weak. It is concluded that Lyrische Symphonie shows Zemlinsky as a sensitive indicator of the tensions which existed between romanticism and ‘Neue Musik’ in the period which Carl Dahlhaus has termed ‘Die musikalische Moderne’.